Chapter Il testamento di Ercole I d'Este - Maire Vigueur, Jean-Claude (Reti Medievali E-Book, 2021)
On the 1st of July 1504, Ercole d'Este, duke of Ferrara (1471-1505), dictated his last will. His testament (that will be published here for the first time) has two main features of interest. Apart from designating Ercole's first son, Alfonso, as his heir, Ercole establishes here the principle of male and legitimate birth right as the only rule for future successions within the Este dynasty. He also leaves to the three unmarried sons - and only to them - an amount of resources big enough to guarantee them a decent way of life. Such resources were provvigioni (in the form of sums of money, fiscal revenues and rural properties) rich enough to let them live such as princes.